Odpowiedź :
Odpowiedź:
[tex]a)\\\\2x=5\ \ /:2\\\\x=\frac{5}{2}\\\\x=2\frac{1}{2}\\\\\\b)\\\\3x+2=8\\\\3x=8-2\\\\3x=6\ \ /:3\\\\x=2\\\\\\c)\\\\\frac{2}{3}x-5=21+2x\ \ /*3\\\\2x-15=63+6x\\\\2x-6x=63+15\\\\-4x=78\ \ /:(-4)\\\\x=-\frac{78}{4}\\\\x=-\frac{39}{2}\\\\x=-19\frac{1}{2}[/tex]
[tex]d)\\\\3(x+2)=2x+1\\\\3x+6=2x+1\\\\3x-2x=1-6\\\\x=-5\\\\\\e)\\\\\frac{2}{5}x-2=\frac{1}{3}x+3\ \ /*15\\\\6x-30=5x+45\\\\6x-5x=45+30\\\\x=75[/tex]
[tex]f)\\\\3(x+2)+2(x-5)=12+3x\\\\3x+6+2x-10=12+3x\\\\5x-4=12+3x\\\\5x-3x=12+4\\\\2x=16\ \ /:2\\\\x=8[/tex]
Odpowiedź:
a) 3x-2 (x+1)=3+3x
3x-2x+2=3+3x
x+2=3+3x/-2
x=1+3x/-3x
-2x=1/:(-2)
x=-1/2
b) 5(x-1)+2x=2(x+1)+8
5x-5+2x=2x+2+8
3x-5=2x+10/+5
3x=2x+15/-2x
x=15
c) 2(4-x)=5 (x-1)-1
8-2x=5x-5-1
8-2x=5x-6/-5x
8-7x=-6/-(-8)
-7x=2/:(-7)
x=-2/7
d) 2 (x-1)-5=3(2x-3)-8x
2x-2-5=6x-9-8x
2x-7=-2x-9/+2x
4x-7=-9/+7
4x=-2/:4
x=-2/4
e) 12x-(2x+1)=9(2-x)
12x-2x-1=18-9x
10x-1=18-9x/+1
10x=19-9x/+9x
19x=19/:19
x=1
f) 3(x+1)-4=2(x-2)+2x
3x+3-4=2x-4+2x
3x-1=4x-4/-4x
-x-1=-4/+1
-x=-3/:(-1)
x=3